Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan: Kajian Literatur - Wahyu Aji Saputro; Dwi Sri Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Leadership style is one of the most influential factors on employee performance in an organization. This literature review analyzes various leadership theories and their impact on employee outcomes. Studies show that transformational leadership significantly improves motivation and productivity, while authoritarian styles may hinder team cohesion. The paper aims to present a comprehensive understanding of how leadership behavior correlates with employee performance based on previous empirical studies